INTEGRASI PENDEKATAN PSIKOLOGI KELUARGA DALAM FAKTOR-FAKTOR PENENTU KEBERHASILAN MEDIASI PERKARA PERCERAIAN DI PENGADILAN AGAMA BINJAI - Wahyuni Firnanda; Khairul Mufti Rambe (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study analyzes the influence of family psychology on the factors determining the success of mediation in divorce cases at the Binjai Religious Court. Recent BPS data show that divorce cases in Indonesia remained high, reaching 394,608 cases in 2024, which reinforces the urgency of examining mediation effectiveness in family disputes. This research employs a normative juridical method with statutory, conceptual, and case approaches by examining divorce case documents and mediation reports from the Binjai Religious Court in 2024. The findings indicate that the success of mediation is influenced by several interrelated factors, including the good faith of the disputing parties, the competence of the mediator, the availability of adequate mediation facilities, and the psychological conditions of the parties involved. In family disputes, conflicts are not merely legal in nature but are also shaped by emotional dynamics, ineffective communication patterns, and psychological wounds that often hinder the achievement of mutual agreements. Therefore, integrating a family psychology approach into the mediation process becomes a strategic step to enhance the effectiveness of family dispute resolution. This approach enables mediators to better understand the emotional conditions of the disputing parties, facilitate more constructive communication, and consider the best interests of all family members, particularly children. Consequently, mediation functions not only as a legal dispute resolution mechanism but also as a means to minimize the psychological impact of divorce and promote a more humane and sustainable conflict resolution process